Technical and vocational skills (TVS): a means of preventing violence among youth in Nigeria - Wan Mohamed, Wan Azlinda; Ibrahim, Mohammed (Universiti Putra Malaysia Press, 2017)
Technical and vocational skills are an important tool for reducing violence among youth, especially in Nigeria, who face security challenges due to different kinds of violence. This paper focusses on the policies and programmes intended to provide youth with skills that can help them improve their life instead of engaging in violence. The paper also studies youth participation in violence. The study shows that youth in Nigeria participate in violence because of unemployment and economic pressure. These youth are mostly from poor families and are mostly used by others to achieve their own unlawful ambition. The data were collected from various secondary sources such as textbooks, journals and conference papers that were carefully reviewed. The results obtained from the literature revealed that youth are not committed, sensitised and mobilised to taking advantage of the opportunities available to them. The results also revealed that almost all the programmes meant to provide youths with skills have failed. Poverty alleviation programmes established to create jobs, self-employment and self-reliance have been unsuccessful. Therefore, alternatives must be provided to help the younger generations. Based on the literature reviewed, the paper discusses related issues and outcomes and ends with recommendations to improve the situation.